A sociolinguistic study: a contrastive analysis of the advertisements of private and public institutions in Pakistan - mahmood, Anser; Hafsa, Ghulam; Zahra, Irum; Tallat, Maha (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
It is a qualitative study and aims at providing an in depth analysis of promotional discourse in academic settings, with the focus on the analysis of powerful and hegemonic use of language to publicize, persuade and to hit specific audience, who aspire high to become iconic managers in competitive economic world. Â Furthermore, the analysis of interdiscursivity as a sign of social change and transitional period. In order to analyze the commercialization of academic discourse of private intuitions of Pakistan, the contrastive analysis, of the advertisements of a private and a public institution, is focused to highlightÂ  that the promotional and consumer discourse places consumption in the central position, in the life of people. The comparative analysis of public and private sector not only highlights the marketizing effect on private sector, but also confirms that public institutions in Pakistan still preserve scholarly and academic discourse. They need not to promote and publicize themselves as the previous result and the fame of the institution are the proof of quality edducatin.As it is a sociolinguistic study so, the analysis also reflects the social post modernity transitional period of Pakistani society.